Maternal virus infections in pregnancy and type 1 diabetes in their offspring: Systematic review and meta‐analysis of observational studies. (22nd March 2018) - Allen, Digby W.; Kim, Ki Wook; Rawlinson, William D.; Craig, Maria E.
Summary: Virus infections are implicated in the development of type 1 diabetes based on epidemiological, clinical, in vitro cell‐based and molecular studies, and animal models. We reviewed the association between virus infections in pregnant women and development of islet autoimmunity or type 1 diabetes in their offspring. We performed a systematic review and meta‐analysis, analysed using random effects models, of human studies from Medline and EMBASE without language restriction. Inclusion criteria were as follows: cohort and case‐control studies measuring viral nucleic acid in blood, stool, urine, or tissue, or serological tests for viruses, in pregnant women whose offspring developed islet autoimmunity and/or type 1 diabetes. All studies required sufficient data to calculate odds ratios and 95% confidence intervals. The 10 studies (4 case control, 6 nested‐case control) that met the eligibility criteria included 2992 participants (953 offspring, 2039 mothers), with varying study design. The 2 outcomes examined were islet autoimmunity ( n  = 466) and type 1 diabetes ( n  = 2526). Meta‐analysis showed a significant association between virus infection during pregnancy and clinical type 1 diabetes during childhood (odds ratio 2·16, 95% CI 1·22‐3·80; P  = 0·008; heterogeneity X 2  = 1·65, I 2  = 40%), but no association with islet autoimmunity (1·45, 0·63‐3·31; P  = 0·38; X 2  = 1·34, I 2  = 25%). The increased risk of type 1 diabetes following maternal virus infection is consistent with viraemia involving the fetus during pregnancy and suggests a potential causative link between antenatal infection and type 1 diabetes. Larger prospective birth studies with more frequent sampling, and pathogenesis studies, are required to more clearly establish an aetiological link.